Readiness to Engage in Interreligious Dialogue Test – internal structure, reliability and validity. Issue 6 (2nd July 2020) - Rydz, Elżbieta; Piotr Bartczuk, Rafał; Zarzycka, Beata; Wieradzka-Pilarczyk, Anna
ABSTRACT: The aim of this paper is to present the internal structure of the Readiness to Engage in Interreligious Dialogue Test (REIDT). The definition of a dialogue in a democratic society forms the theoretical framework for the test construction. The readiness to engage in interreligious dialogue was defined as a mental readiness to exchange views on religious topics, based on a symmetrical exchange of thoughts, aimed at creation of mutual understanding by people with different religious affiliations, involved in cooperation to meet this objective. The REIDT consists of 36 items, factor analysis revealed four dimensions of interreligious dialogue: readiness to exchange views on religious topics, readiness to seek mutual understanding, internal barriers for the symmetry of a dialogue, and readiness to communicate with representatives of other religions. The paper includes a brief description of the stages of work on the structure of the method and the reliability and validity indicators.